Tailoring structural and electrochemical properties in Sr2+ incorporated nanostructured BiFeO3 for enhanced asymmetric solidstate supercapacitor. (20th July 2022) - Tripathi, Himadri Sekhar; Dutta, Alo; Sinha, T.P.
Highlights: Rietveld refinement of X-ray diffraction patterns suggested the coexistence of rhombohedra R3c and Pseudo-tetragonal P4/mmm phases for 20% Sr 2+ incorporation in nanostructured BiFeO3 (BFO). SBFO-30 appears to be the best electrode material exhibiting specific capacitance in the range of 1200 F/g at 1 A/g with 89% capacity retention even after 5000 cycles at 5 A/g. Solidstate asymmetric supercapacitor (ASC) fabricated with SBFO-30//Ni-foam as the positive electrode and carbon nanotube (CNT)//Ni-foam as the negative electrode. This ASC exhibits specific capacitance as high as 273 F/g at 1 A/g which correspond to the energy and power densities of 97 Wh/Kg and 6.56 KW/Kg, respectively. Abstract: Optimization of the electrochemical performance of electro-active species is significantly helpful for fabrication of high performance energy storage device. Since, Bi 3+ (A-site) shows electrochemically active features, then energy storage capacity is further improved by Sr 2+ doping at A-site. In this work, Srx Bi1-x FeO3 (0.05≤ x  ≤ 0.5) nanostructured electrode materials are synthesized by hydrothermal route. X-ray diffraction (XRD) pattern suggested the coexistence of rhombohedral R3c and tetragonal P4/mmm phases for 20% Sr 2+ incorporation in nanostructured BiFeO3 (BFO), which is further correlated with Raman spectroscopy. Of the different Sr 2+ concentration investigated, the 30% Sr 2+ doped BiFeO3 (SBFO-30) appears to be the best electrode material exhibiting specific capacitance in the range of 1200 F/g at 1 A/g with 89% capacity retention even after 5000 cycles at 5 A/g. Further, solidstate asymmetric supercapacitor (ASC) fabricated with SBFO-30//Ni-foam as the positive electrode and carbon nanotube (CNT)//Ni-foam as the negative electrode exhibited specific capacitance as high as 273 F/g at 1 A/g corresponding to the energy and power densities of 97 Wh/Kg and 6.56 KW/Kg, respectively. Thus, among the all investigated electrode materials, SBFO-30 clearly emerged as an excellent electrode material for supercapacitor applications. Graphical abstract: Image, graphical abstract